Development of a Construct 2-Based Platformer Game: Challenges and Implementation for Players of All Ages - Elistatia, Usi; Permatasari, Sisca; Permatasari, Intan (Gameology and Multimedia Expert, 2024)
This study aims to develop a Construct 2-based platformer game designed to provide an interactive and challenging gameplay experience for players of all ages. The game features key elements such as character movement, object collection missions, and enemy obstacles that players must avoid. The development process involved multiple stages, including requirements analysis, prototype creation, and alpha and beta testing. A scoring and life system was also implemented to enhance gameplay appeal and increase the challenge. Testing and feedback from external players helped refine control elements and level design. The final results demonstrate that this platformer game delivers an enjoyable experience while enhancing players' critical thinking and problem-solving skills. Construct 2 proved to be an effective platform for developing simple yet high-quality games.